Geodynamic seawater-sediment porewater evolution of the east central Atlantic Paleogene ocean margin revealed by U-Pb dating of sedimentary phosphates - Aubineau, Jérémie; Parat, Fleurice; Chi Fru, Ernest; El Bamiki, Radouan; Mauguin, Olivia; Baron, Fabien; Poujol, Marc; Séranne, Michel (Frontiers in Earth Science, 2022)
Emerging evidence suggests that U-Pb and Lu-Hf ages of sedimentary apatite group minerals are often younger than their biostratigraphic ages. However, U-Pb dating of exquisitely preserved carbonate fluorapatite (CFA) is rare. The Upper Cretaceous/Paleogene marine sedimentary rocks of the Moroccan High Atlas host phosphate-rich sediments bracketed by calcareous nannofossil Zones (NP4-NP9) of late Danian to Thanetian age. Here, we use a laser-ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) to decipher whether CFA minerals are suitable for U-Pb chronostratigraphy and whether they can reveal the sedimentary and seawater history from which they formed. U-Pb dating of the CFA grains yields ages of 42.9 ± 1.3 Ma (MSWD = 2.3) and 35.7 ± 2.8 Ma (MSWD = 1.3) from three distinct phosphate-rich beds, being >15 million years younger than the expected biostratigraphic age. Combined scanning electron microscopy, X-ray diffraction, and infrared spectroscopy analyses, associate the Mg-rich clay minerals sepiolite and palygorskite, with micro-CFA crystals, while LA-ICP-MS trace element, rare earth element, and yttrium content for primary CFA grains, collectively point to long-term early diagenetic adsorption from oxygenated seawater-dominated porewater fluids. Authigenic clay minerals display a seawater-like pattern, with negligible U concentrations suggesting limited clay mineral influence on U-Pb dating of the CFA crystals. Considering the absence of extensive post-depositional alteration, we propose that because of their large surface area, the µm-sized CFA crystallites facilitated real-time surface adsorption and desorption of elements and diffusion processes. These conditions generated long-term open system connection of sediments with overlying seawater, enabling continuous U-Pb exchange for 15–25 Myr after phosphate precipitation. The data suggest that system closure was potentially associated with sediment lithification and the Atlas orogeny, pointing to stable oxygenation of shallow marine waters along the eastern passive margin of the central Atlantic Ocean in the Paleogene.